2001
DOI: 10.1002/cbf.899
|View full text |Cite
|
Sign up to set email alerts
|

Control of apolipoprotein E secretion in the human hepatoma cell line KYN‐2

Abstract: Even though it is known that apolipoprotein E (apoE) is deeply involved in major age-related disorders such as atherosclerosis or Alzheimer's disease (AD), the control of cell-specific apoE expression is still poorly understood. We compared the apoE secretion as previously described in astrocytic cell17 to hepatic cell apoE secretion. We used the human hepatoma cell line KYN-2 to better delineate the characteristics of apoE secretion and to validate it with respect to the classical human hepatoma cell line Hep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Cellular models are widely used to study gene expression profiling. For example, it was shown that Kyn2 and HepG2 cells express active peroxisome proliferator-activated receptor gamma (Rumi et al 2001) and apolipoprotein E (Brahimi et al 2001). Studies have been interested into cell line genetic profiles in order to correlate them with expression of diverse phenotypes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cellular models are widely used to study gene expression profiling. For example, it was shown that Kyn2 and HepG2 cells express active peroxisome proliferator-activated receptor gamma (Rumi et al 2001) and apolipoprotein E (Brahimi et al 2001). Studies have been interested into cell line genetic profiles in order to correlate them with expression of diverse phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…They permit biochemical characterization of a number of pathways, in conditions resembling physiologic or pathologic conditions (Brahimi et al 2001;Fach et al 2004;Riou et al 2007). Cell lines also help to study a response to drugs by providing information on their efficacy, toxicity, and mechanisms of action.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the inhibition of VLDL secretion by HCV core protein or a mutation of apoE causes apoE to accumulate in HCC tissues. ApoE is produced and secreted by human hepatoma cell lines (32,33) as well as by fetal liver (27), and the expression of apoE increases during embryonic development in zebrafish (34). Moreover, oxidative stress in HCC tissues (35) causes high levels of apoE expression because apoE functions as an anti-oxidant, and apoE mRNA expression increases in prostate cancers with high malignant potential (20), in gastric (21) and ovarian cancers (22).…”
Section: Discussionmentioning
confidence: 99%
“…This oxysterol affects expression of the cholesterol efflux pumps ATP-binding cassette transporter (ABC)A1 [9] and ABCG1, and expression of apolipoprotein E [1012]. 25-OHC is able to stimulate LXR-independent oligodendrocyte apoptosis and suppresses myelin gene expression in peripheral nerves via LXR/Wnt/β-catenin-mediated pathways [13].…”
Section: Introductionmentioning
confidence: 99%